2017
DOI: 10.1016/j.bbamem.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated chains in asymmetric lipids disorder raft mixtures and preferentially associate with α-Synuclein

Abstract: Using molecular dynamics simulations, we have explored the effect of asymmetric lipids—specifically those that contain one polyunsaturated (PUFA) and one saturated fatty acid chain—on phase separation in heterogeneous membranes. These lipids are prevalent in neuronal membranes, particularly in synaptic membranes, where the Parkinson's Disease protein α-Synuclein (αS) is found. We have therefore explored the relationship between asymmetric, PUFA-containing lipids, and αS. The simulations show that asymmetric li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…However, not every lipid can trigger α-synuclein aggregation, as the length of the acyl chain is critical for the aggregation. Only short and saturated hydrocarbon chains [64] were shown to be able to induce α-synuclein aggregation, whereas polyunsaturated fatty acids [65] form stable multimers with α-synuclein. Therefore, it appears that α-synuclein aggregation may either be enhanced or quenched according to the kind of fatty acid it binds to.…”
Section: Fatty Acidsmentioning
confidence: 98%
“…However, not every lipid can trigger α-synuclein aggregation, as the length of the acyl chain is critical for the aggregation. Only short and saturated hydrocarbon chains [64] were shown to be able to induce α-synuclein aggregation, whereas polyunsaturated fatty acids [65] form stable multimers with α-synuclein. Therefore, it appears that α-synuclein aggregation may either be enhanced or quenched according to the kind of fatty acid it binds to.…”
Section: Fatty Acidsmentioning
confidence: 98%
“…Follow up studies have further explored the properties of these domains as a function of lipid composition, 315322 including the effect of hybrid lipids (lipids with one saturated and one unsaturated tail) that act as linactants (i.e., decrease the line tension between the domains). 323327 Making use of high-throughput simulation strategies, complete lipid phase diagrams can nowadays be established, for example, for binary lipid/cholesterol systems as a function of temperature, 328,329 as well as ternary and even quaternary mixtures. 330334 Figure 3 provides an example of a ternary phase diagram from Carpenter et al 335 based on the Martini model, in comparison to the experimental phase diagram.…”
Section: Increasing Complexitymentioning
confidence: 99%
“…An important breakthrough was reported by Risselada and Marrink, who simulated the spontaneous formation of Lo and Ld domains in ternary mixtures of saturated and unsaturated lipids together with cholesterol based on the Martini model. Follow up studies have further explored the properties of these domains as a function of lipid composition, including the effect of hybrid lipids (lipids with one saturated and one unsaturated tail) that act as linactants (i.e., decrease the line tension between the domains). Making use of high-throughput simulation strategies, complete lipid phase diagrams can nowadays be established, for example, for binary lipid/cholesterol systems as a function of temperature, , as well as ternary and even quaternary mixtures. Figure provides an example of a ternary phase diagram from Carpenter et al based on the Martini model, in comparison to the experimental phase diagram . In the study of Ackerman and Feigenson, concentrations of DPPC and cholesterol are fixed, whereas the nanodomain-inducing lipid 16:0,18:2-PC (PUPC) is incrementally replaced by the macrodomain-inducing lipid 18:2,18:2-PC (DUPC).…”
Section: Increasing Complexitymentioning
confidence: 99%
“…Likewise, mitochondria, an important organelle, may be due to the decrease of ATP and the increase of reactive oxygen species due to SVE dysfunction, which further leads to the onset of PD ( Nguyen et al, 2019 ). In the study of lipids, studies have shown that the possibility of lipid rafts is also involved in the aggregation and positioning of α-synuclein ( Brummel et al, 2017 ). Dysregulation of lipid rafts-dependent endocytosis may caused cell-to-cell transmission of α-synuclein was facilitated ( Cha et al, 2015 ).…”
Section: Other Pathways Involved In Regulation By Svementioning
confidence: 99%